Hypothermic machine perfusion is superior to static cold storage in deceased donor kidney transplantation: A meta‐analysis. Issue 4 (5th March 2020) - Tingle, Samuel J.; Figueiredo, Rodrigo S.; Moir, John AG.; Goodfellow, Michael; Thompson, Emily R.; Ibrahim, Ibrahim K.; Bates, Lucy; Talbot, David; Wilson, Colin H.
Abstract: Background: There remains a lack of consensus on the optimal storage method for deceased donor kidneys. This meta‐analysis compares storage with hypothermic machine perfusion (HMP) vs traditional static cold storage (SCS). Methods: The Cochrane Kidney and Transplant Specialised Register was searched to identify (quasi‐) randomized controlled trials (RCTs) to include in our meta‐analysis. PRISMA guidelines were used to perform and write this review. Results: There is high‐certainty evidence that HMP reduces the risk of delayed graft function (DGF) when compared to SCS (2138 participants from 14 studies, RR = 0.77; 0.67‐0.90, P  = .0006). This benefit is significant in both donation following circulatory death (DCD; 772 patients from seven studies, RR = 0.75; 0.64‐0.87, P  = .0002) and donation following brainstem death (DBD) grafts (971 patients from four studies, RR = 0.78; 0.65‐0.93, P  = .006). The number of perfusions required to prevent one episode of DGF was 7.26 and 13.60 in DCD and DBD grafts, respectively. There is strong evidence that HMP also improves graft survival in both DBD and DCD grafts, at both 1 and 3 years. Economic analyses suggest HMP is cost‐saving at 1 year compared with SCS. Conclusion: Hypothermic machine perfusion is superior to SCS in deceased donor renal transplantation. Direct comparisons with normothermic machine perfusion in RCTs are essential to identify optimal preservation methods in kidney transplantation.